SPE Annual Technical Conference and Exhibition 2001
DOI: 10.2118/71495-ms
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Effects in Gas-Condensate Recovery and Gas Injection Processes

Abstract: Gas condensate production and gas injection processes are strongly influenced by the gas/oil (or condensate) interfacial tension and by the wetting behavior of oil on the porous substrate. Oil (condensate) recovery is favored by low gas/oil (condensate) interfacial tensions and by complete wetting of oil (condensate)on the water phase that often covers the porous rock. The relevant parameters are dimensionless numbers that measure the importance of the oil/gas interfacial tension relative to gravity (Bond numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Previous studies [6,9] confirmed this trend. Melean et al [9] studied the effects of thermodynamic conditions on the interfacial properties.…”
Section: Figuresupporting
confidence: 76%
See 2 more Smart Citations
“…Previous studies [6,9] confirmed this trend. Melean et al [9] studied the effects of thermodynamic conditions on the interfacial properties.…”
Section: Figuresupporting
confidence: 76%
“…Previous studies [6,9] confirmed this trend. Melean et al [9] studied the effects of thermodynamic conditions on the interfacial properties. Relevant parameters which they studied are dimensionless Bond number and capillary number to relative interfacial properties to gravity and viscous forces, respectively.…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…The following mechanisms have been mentioned in the literature: (a) oil viscosity reduction; (b) oil swelling; (c) solution gas drive; (d) relative permeability hysteresis due to reduced water saturation, drainage/imbibition, and wettability alternation; (e) repressurization; (f) diffusion; and (g) interfacial tension reduction in the zone near the wellbore. (5)(6)(7) …”
Section: Introductionmentioning
confidence: 99%
“…In this state, the efficiency of oil recovery by drainage from a model reservoir is also similar to that from a system in the complete wetting state [3]. On grounds of dynamic arguments, however, one expects considerable differences to the flow in a system with a truly macroscopic wetting layer [14]. Therefore, accurate knowledge of both transition temperatures is highly desirable.…”
Section: Introductionmentioning
confidence: 99%